2014
DOI: 10.1366/14-07505
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Chip Development Using Infrared Imaging for the Identification of Catfish Species

Abstract: Several families of catfish species are extensively aquacultured around the world; however, only those from the family Ictaluridae can be labeled as catfish in the United States. Non-Ictalurid catfish species that are marketed as "catfish" in the USA are considered misbranded. Misbranding in general has led to an increased interest in developing deoxyribonucleic acid (DNA)-based methods such as DNA barcoding, polymerase chain reaction restriction fragment length polymorphism, and DNA microarrays with fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…These advanced methods of DNA barcoding have been applied in unknown species identification, point mutations, biodiversity assessment and food security (Trivedi et al 2016). Handy et al (2014) identified reported misidentification of seven catfish species in USA seafood market by using DNA microarrays with newly developed mid-infrared imaging detection method.…”
Section: Microarraysmentioning
confidence: 99%
“…These advanced methods of DNA barcoding have been applied in unknown species identification, point mutations, biodiversity assessment and food security (Trivedi et al 2016). Handy et al (2014) identified reported misidentification of seven catfish species in USA seafood market by using DNA microarrays with newly developed mid-infrared imaging detection method.…”
Section: Microarraysmentioning
confidence: 99%
“…The world of eukaryotic DNA-based species identification in food and dietary supplements products has undergone a revolution in the past 10 years, and while progress has been swift it has not been without challenges [8][9][10]. Contemporary methods of DNAbased identification include DNA fingerprinting techniques like restriction fragment length polymorphisms [11], microarrays [12], a full suite of polymerase chain reaction (PCR) methods, [13][14][15][16][17], in addition to traditional DNA barcoding [9,18] and a variety of next generation sequencing (NGS) approaches [19][20][21].…”
Section: Introductionmentioning
confidence: 99%